Acute Diffuse Peritonitis Caused by Urinary Retention: A Rare Case of Gangrenous Cystitis - Konstantinos Kotoulas; Chrysostomos Georgellis; Engkin Kigitzi; Apostolos Liappis; Marios Spounos; Vasiliki Tsalkidou; Emmanouil Patris (Case Reports in Urology)
Gangrenous cystitis is an umbrella term encompassing conditions from necrosis of the mucosa and submucosa to necrosis of the entire bladder wall that can result in acute peritonitis. Timely diagnosis is challenging as the symptoms are nonspecific and resemble other conditions such as cystitis. We report a case of gangrenous cystitis in a 63-year-old woman who was diagnosed with peritonitis preoperatively by a CT scan of the abdomen. Overdistension of the bladder due to chronic urinary retention was the primary cause. The patient underwent partial cystectomy, excising nonviable detrusor with preservation of the trigone and ureters, but conclusively succumbed. Etiopathology, symptoms, and treatment of this rare disease are also considered.